Blood-pressure and cholesterol lowering in persons without cardiovascular disease - Yusuf, Salim; Phi, D.; Lonn, Eva; Pais, Prem; Bosch, Jackie; López‑Jaramillo, Patricio; Md Aris, Mohd Aznan; Mohd Shah, Azarisman Shah; ., et. al (Massachusetts Medical Society, 2016)
Elevated blood pressure and elevated low-density lipoprotein (LDL) cholesterol increase the risk of cardiovascular disease. Lowering both should reduce the risk of cardiovascular events substantially.